Natural assets : (Island Press, 2003)
Low-income communities frequently suffer from a lack of access to, or lack of control over, the natural resources that surround them. In many cases, their local environment has been degraded by years of resource extraction and pollution by distant corporations or government agencies. In such settings, initiatives that build natural assets in the hands of the poor can play an important role in poverty-fighting efforts.